2020
DOI: 10.7150/jca.40974
|View full text |Cite
|
Sign up to set email alerts
|

IL22 drives cutaneous melanoma cell proliferation, migration and invasion through activation of miR-181/STAT3/AKT axis

Abstract: Cutaneous melanoma (CM) is neoplastic growth of melanocytes with strong potential to proliferate and invade, prone to a fatal disease soon which is beyond surgical clearance. The use of regulator involving in antitumor immune responses has been identified as a potential therapeutic option for CM, but still need fully understood at present. Recently, interleukin 22 (IL22), an immune molecule secreted mostly by CD4 + T cells, was reported having functions in a variety of human diseases including encouragement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…STAT3 is known to be constitutively activated in various types of cancer (9), such as cutaneous melanoma (10), squamous cell carcinoma (11) and oral squamous cell carcinoma (12). In addition to promoting angiogenesis, STAT3 regulates cell proliferation, migration and invasion of tumor cells, indicating its crucial role in the control of tumor growth and metastasis (10,(40)(41)(42). The present study demonstrated that STAT3 inhibitor C188-9 attenuated the expression of EMT-promoting mRNA levels.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…STAT3 is known to be constitutively activated in various types of cancer (9), such as cutaneous melanoma (10), squamous cell carcinoma (11) and oral squamous cell carcinoma (12). In addition to promoting angiogenesis, STAT3 regulates cell proliferation, migration and invasion of tumor cells, indicating its crucial role in the control of tumor growth and metastasis (10,(40)(41)(42). The present study demonstrated that STAT3 inhibitor C188-9 attenuated the expression of EMT-promoting mRNA levels.…”
Section: Discussionsupporting
confidence: 55%
“…STAT3 transduces signals from the cell membrane receptors to the nucleus, where it acts as a transcription factor. STAT3 is known to be constitutively activated in various types of cancer (9), such as cutaneous melanoma (10), squamous cell carcinoma (11) and oral squamous cell carcinoma (12). In addition to promoting angiogenesis, STAT3 regulates cell proliferation, migration and invasion of tumor cells, indicating its crucial role in the control of tumor growth and metastasis (10,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subepithelial lung fibroblast proliferation, transformation to myofibroblasts and synthesis of extracellular matrix are the main mechanisms leading to subepithelial fibrosis in patients with asthma (25,26). IL-22 is an immune-related cytokine that was discovered in previous years and plays a role in the occurrence and development of psoriasis, arthritis and cancer (22,27,28). Previously, it was reported that IL-22 promotes allergic airway inflammation in sensitized mice in vivo (17).…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 has been reported to activate the JAK/STAT3 signaling pathway. Furthermore, STAT3 participates in airway remodeling (22). Therefore, the present study investigated the relationship between airway remodeling and the IL-22/IL-22R1 signaling pathway in bronchial asthma.…”
Section: Introductionmentioning
confidence: 94%